Pengaruh Efektivitas Sistem Informasi Akuntansi pada Kinerja Karyawan dengan Insentif dan Motivasi Kerja sebagai Pemoderasi - Prariadena, Chandrika Hutami; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi, 2019)
This study aims to   determine the   effect of the effectiveness of accounting information   systems on employees’ performance with incentives and work motivation as moderators in Denpasar LPD. The population of this study was employees at the 35 LPDs in Denpasar. The sample was determined by using a purposive   sampling method   with a total   sample of   99 people. The methods of data   collection were done by using questionnaire method and simple linear regression data analysis   techniques and moderation regression   analysis. Based on the   results of   the analysis found that the effectiveness   of accounting information   systems have positive effects on employees’ performance   such as incentives weaken the effectiveness   of accounting   information systems on employee performance and work motivation reinforces the   effectiveness of accounting   information systems on employee performance   in Denpasar LPD. Keywords   :  Effectiveness   of accounting   information systems, incentives, work motivation employee performance